EKSISTENSI SUYARTO SEBAGAI SINDEN LANANG: SEBUAH BIOGRAFI - Endah Ayu Prasetyo; Prasadiyanto Prasadiyanto; Slamet Riyadi (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
This article antitled “The existence of Suyarto As a Sinden Lanang:a Biography” is based on the research by Endah Ayu Prasetyo, primarily examines the existence of Suyarto as a sinden lanang who existed in between 1995-2006.  There are two important issues subject to discussion which are 1) how was the process oftransforming and developing artistry of Suyarto as a sinden lanang until he became famous? and 2) why in between 1995 and 2006 Suyarto’s name was known as sinden lanang?.  Suyarto, who came from a farming family and only attended elementary school, was able to become a successful male sinden in 1995-2006. This research  describes Suyarto’s artistic experience to reach his existence.  The study uses a historical approach by Kuntowijoyo, especially biographies which examine the character’s personality, supportive social forces, historical circumstances of his era, and luck and opportunity. This thought is synergized with Alvin Boskoff’s theory, that a change is influenced by internal and external factors.Collecting the necessary data was carried out by following qualitative research procedures and oral history. Apart from literary data and artifacts, the informants’ testimonies against Suyarto are also a very important source of data in this research.